Analisis dampak alih fungsi lahan subak terhadap kerawanan bencana banjir: (Studi kasus di desa Jatiluwih, kecamatan Penebel, kabupaten Tabanan, provinsi Bali) - Vitiara, Mustarini Dessy; Putri, Annysa Arientika; Triadi, Januar (Social Agriculture, Food System, and Environmental Sustainability, 2024)
Subak is a local wisdom in Bali in the form of a socio-cultural agrarian system for the management of rice fields with irrigation or irrigation systems regulated by members of the Subak group. In its management, Subak land tends to experience degradation due to external interventions as tourism interest grows in Bali. The conversion of land to increase tourism facilities in Bali leads to a decrease in the area of rice fields managed with the Subak system. In the research location, namely Jatiluwih Village, Penebel District, Tabanan Regency, land degradation is identified due to the transformation of agricultural land into non-agricultural land such as hotels or homestays and restaurants to support the tourism sector. Previous research recorded the presence of 10 homestay units and restaurants with medium to large land use sizes on the main road in Jatiluwih Village. This number will continue to increase depending on the promotion and continuous tourism interventions, resulting in ongoing land conversions. Based on spatial observations, rice fields with the Subak system in Jatiluwuh Village cover an area of ​​360 hectares integrated with a river flow along 80 kilometers. The rainfall in Jatiluwih Village falls under the very high category, which is >500mm. This further reinforces the potential for flooding if the existing land is not well managed. So far, there have been no reports of flooding in Jatiluwih Village due to the overflowing of water in the fields caused by long rainy seasons or storms. However, continuous tourism expansion as a result of Subak being designated as one of UNESCO's Intangible Cultural Heritage in 2012, has the potential to further reduce the area of ​​rice fields with the Subak system, which play a role in the infiltration and perforation of water into the soil. Policies related to tourism growth while preserving Subak rice fields in Jatiluwih Village need to be balanced, so that their existence can continue, especially in avoiding rice field degradation and preventing the potential for floods.